The Mediating Role of Body Mass Index in the Association Between Age at First Childbirth and Lung Function Among Chinese Postmenopausal Women - Wang, Gaili; Tian, Huizi; Kang, Kai; Feng, Shixian; Shao, Weihao; Chen, Xiaorui; Zheng, Caifang; Zhang, Bowen; Pei, Pei; Zhang, Weidong (Clinical epidemiology, 2023)
Little is known about the effect of age at first childbirth on lung function. We aimed to investigate the association between age at first childbirth and lung function in Chinese women and further test whether this association is mediated by body mass index (BMI). This cross-sectional study is a partial survey of the China Kadoorie Biobank (CKB) which was conducted in Xinxiang City, Henan Province between 2004 and 2008. A total of 16,584 postmenopausal women aged 30-79 years were enrolled. Multiple linear and logistic regression were used to investigate the association between age at first childbirth and lung function and overweight/obesity. The mediation analysis was performed using the PROCESS procedure for SPSS. The mean (SD) age at first childbirth was 23.1 (2.7) years. Women with first childbirth aged ≤19 years and 20-22 years had lower lung function than women who gave first childbirth aged 23-25 years. Per 1-year increase in the age at first childbirth was associated with a 3.31 mL increase in FEV1 (95% CI = 1.27-5.35), 3.91 mL increase in FVC (95% CI = 1.63-6.18), 0.15% increase in FEV1, % predicted (95% CI = 0.05-0.24) and 0.14% increase in FVC, % predicted (95% CI = 0.05-0.22). There was no clear association between age at first childbirth and FEV1/FVC ratio. BMI played a contribution to the association between age at first childbirth and FEV1 and the proportion was 16.4% (indirect effect: β = 0.65, 95% CI = 0.46-0.89; total effect: β = 3.96, 95% CI = 1.92-5.99). Similarly, the proportion to FVC, FEV1, % predicted, and FVC, % predicted was 25.0%, 16.6%, and 25.0%, respectively. Early age at first childbirth was associated with lower lung function and BMI mediated the association. It is important to test lung function and popularize the knowledge of weight control in women who gave first childbirth at an early age.